IMPLEMENTATION OF BARONE-ADESI AND WHEY MODEL IN FORCASTING FUTURES AND OPTIONS PRICE - Rantung, Danny Ivan (JBE (Journal of Business and Economics); Volume 7 No.2, 2008 JBE UNKLAB, 2008)
This study develops a method for estimating confidence intervals surrounding futures based forecasts of natural gas prices. The method utilizes the Barone-Adesi and Whaley model for option valuation to "back-out" the market's assessment of the annualized standard deviation of natural gas futures prices. The various implied standard deviations are then weighted and combined to form a single weighted implied standard deviation following the procedures outlined by Chiras and Manaster. This option implied weighted standard deviation is then tested against the more traditional "historical" measure the standard deviation. The paper then develops the procedure to transform the weighted standard deviation and futures price into a price range at the option expiration date. The accuracy of this forecast is then tested against 15 and 30 day average forecasts.